2017
DOI: 10.1002/polb.24395
|View full text |Cite
|
Sign up to set email alerts
|

Electrohydrodynamics of spherical polyampholyte-grafted nanoparticles: Multiscale simulations by coupling of molecular dynamics and lattice-boltzmann method

Abstract: We perform multiscale simulations based on the coupling of molecular dynamics and lattice-Boltzmann (LB) method to study the electrohydrodynamics of a polyampholyte-grafted spherical nanoparticle. The long-range hydrodynamic interactions are modeled by coupling the movement of particles to a LB fluid. Our results indicate that the netneutral soft particle moves with a nonzero mobility under applied electric fields. We systematically explore the effects of different parameters, including the chain length, graft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…7a). This is different from spherical polyelectrolyte or polyampholyte brushes, 25,26 which adopt signicantly extended conformation along the ow direction (or the direction of the electric eld). The enhancement of the electric eld causes the increase of the parallel component (Fig.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…7a). This is different from spherical polyelectrolyte or polyampholyte brushes, 25,26 which adopt signicantly extended conformation along the ow direction (or the direction of the electric eld). The enhancement of the electric eld causes the increase of the parallel component (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…[18][19][20][21][22][23][24] Recently, electrophoresis of spherical colloids graed with charged polymers (such as polyelectrolytes and polyampholytes) was also studied by means of molecular dynamics (MD) simulations considering longranged hydrodynamic interactions based on lattice-Boltzmann method. 25,26 Nonzero electrophoresis mobility was observed for net-neutral particles. For graed polyampholytes, we found that the mobility of the net-neutral particles remarkably depends on the structures of the polymer layer.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we briefly introduce the method, and interested readers are referred to our previous studies and other refs [ ] for the details of the algorithm. In the LB method, the central quantity of the algorithm is f i ( x⃗ , t ), which is used to describe the solvent distribution at the lattice site x⃗ and time t .…”
Section: Models and Simulation Methodsmentioning
confidence: 99%